2017
DOI: 10.1038/ncomms15541
|View full text |Cite
|
Sign up to set email alerts
|

Airborne observations reveal elevational gradient in tropical forest isoprene emissions

Abstract: Isoprene dominates global non-methane volatile organic compound emissions, and impacts tropospheric chemistry by influencing oxidants and aerosols. Isoprene emission rates vary over several orders of magnitude for different plants, and characterizing this immense biological chemodiversity is a challenge for estimating isoprene emission from tropical forests. Here we present the isoprene emission estimates from aircraft eddy covariance measurements over the Amazonian forest. We report isoprene emission rates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 42 publications
(61 reference statements)
7
60
0
Order By: Relevance
“…1, much of the land cover outside of Manaus is tropical forest, with some pasture land interspersed. Significant isoprene emissions are expected and indeed measured from the forest (Gu et al, 2017;Guenther et al, 2006). Significant concentrations of methacrolein, methyl vinyl ketone, and isoprene hydroxyhydroperoxides (PTR-MS m/z 71), all first-generation oxidation products of isoprene, are also observed and have a more complicated structure (Liu et al, 2016).…”
Section: Wetmentioning
confidence: 94%
“…1, much of the land cover outside of Manaus is tropical forest, with some pasture land interspersed. Significant isoprene emissions are expected and indeed measured from the forest (Gu et al, 2017;Guenther et al, 2006). Significant concentrations of methacrolein, methyl vinyl ketone, and isoprene hydroxyhydroperoxides (PTR-MS m/z 71), all first-generation oxidation products of isoprene, are also observed and have a more complicated structure (Liu et al, 2016).…”
Section: Wetmentioning
confidence: 94%
“…Measurements and models in Gu et al (2017) showed that isoprene emissions were approximately 2 times higher in the dry season than the wet season during this field campaign. We can make the assumption that other biogenic gases (including MT and SQT) also exhibited higher emissions in the dry season.…”
Section: Estimating Source Contributions To Potential Soa Using Multimentioning
confidence: 99%
“…Biogenic volatile organic compound (VOC) emissions from forests vary widely across plant species, ecosystem type, season, time of day, and environmental conditions at many scales, including from tens to hundreds of meters (Gu et al, 2017;Fuentes et al, 2000;Goldstein and Galbally, 2007;Alves et al, 2018;Greenberg et al, 2004;Guenther et al, 2006;Klinger et al, 1998;Kuhn et al, 2004;Pugh et al, 2011;Wang et al, 2011). These variations can have significant effects on and be affected by atmospheric chemistry, air quality, and climate (Chameides et al, 1988;Fuentes et al, 2000;Laothawornkitkul et al, 2009;Goldstein et al, 2009;Kesselmeier et al, 2013;Peñuelas and Staudt, 2010).…”
Section: Introductionmentioning
confidence: 99%